Enhancing consumer knowledge and awareness through nutrition education: A key step in transforming food systems towards consumption of healthier diets - Musita, Consolata; Jordan, Irmgard; Termote, Celine (2023)
Food systems: impact diets hence nutrition outcomes and are complex and involve a wide range of interdependent activities and actors with the consumer at the centre. Consumer choices: influence how they acquire, prepare and consume food and play a significant role in the food system. Empowering consumers: to demand healthier diets provides an opportunity to transform food systems towards healthy diets. HealthyFoodAfrica (HFA): a project that aims to improve diets by reconnecting food production and food consumption in effective ways. This project works in 6 African cities in 10 Food System Labs (FSLs).